2022
DOI: 10.1038/s41746-022-00576-y
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning of language use on Twitter reveals weak and non-specific predictions

Abstract: Depressed individuals use language differently than healthy controls and it has been proposed that social media posts can be used to identify depression. Much of the evidence behind this claim relies on indirect measures of mental health and few studies have tested if these language features are specific to depression versus other aspects of mental health. We analysed the Tweets of 1006 participants who completed questionnaires assessing symptoms of depression and 8 other mental health conditions. Daily Tweets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…Therefore, it is imperative to confirm the robustness and reliability of these structures. It is for this reason that some studies repeatedly interrogate the same factor structure across studies [e.g., AD, CIT, and SW: (30,36,46,68,101,116,120,124)], establishing that the association between dimensions and cognitive measures is replicable [e.g., (30,40)] and that results extend to diagnosed patients (32). While this is vital work, there are risks too in focusing narrowly on a single dimensional structure; specific factors, like disorders, may get reified as novel questionnaires and become difficult to change.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is imperative to confirm the robustness and reliability of these structures. It is for this reason that some studies repeatedly interrogate the same factor structure across studies [e.g., AD, CIT, and SW: (30,36,46,68,101,116,120,124)], establishing that the association between dimensions and cognitive measures is replicable [e.g., (30,40)] and that results extend to diagnosed patients (32). While this is vital work, there are risks too in focusing narrowly on a single dimensional structure; specific factors, like disorders, may get reified as novel questionnaires and become difficult to change.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous depression and suicide detection studies were conducted on social media rather than clinical interviews [ 18 , 19 ]. Social media texts freely generated by users are often nonspecific to suicide or depression [ 22 ]. This study analyzed participants’ responses to the HAMD questions, specifically focusing on a series of depressive symptomatologies.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous evaluation of the efficacy of using various machine learning algorithms to automatically identify emotions expressed on Twitter found that the highest performing algorithm achieved an accuracy rate of 65% [ 14 ]. Another recent article found that machine learning was not effective in making meaningful predictions about users’ mental health from language use on social media; further, Twitter metadata and language use was not specific to any one mental health condition [ 59 ].…”
Section: Discussionmentioning
confidence: 99%